Gender and skill dimensions of technological transitions at workplaces: the case of The Czech Republic, Poland and Slovakia - Mensah, Ebenzer Kwabla; Nchor, Dennis (Zmiany technologiczne w miejscu pracy w kontekście płci i umiejętności. Przypadek Czech, Polski i Słowacji, 2020)
The study seeks to investigate the impact of technology on employment by gender and skills of the labour markets in the Czech Republic, Poland and Slovakia, and employs the VAR model to analyse the impact of technology on employment by gender. It also uses a panel cointegrated autoregressive distributed lag model for the impact of technology on employment by skill groups. The study finds that although technology impacts on employment of gender in the three countries, it is however gender neutral. This study also finds that in the long-term, technology impacts negatively on middle skill employment and positively on low skill and high skill employment in a similar pattern before and after the global financial crises. The impact of technology varies across countries in the short term, attributed to cross-country differences in labour market policies and institutions
Ekonomia XXI Wieku = Economics of the 21st Century, 2020, Nr 23, s. 87-108